Influence of carbon and nitrogen source on growth, DON and NIV production by two species of fusarium isolated from finger millets - Penugonda, Shilpa; Rao, Vankudoth Koteswara; Rao, K. Narasimha; Sivadevuni, Girisham; Reddy, Solipuram Madhusudhan (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: Influence of different carbon [C] and nitrogen [N] source on the growth and Deoxynivalenol [DON] and Nivalenol [NIV] production by Fusarium aethiopicum and Fusarium culmorum was investigated. Methods: Seven days old monosporic cultures of F. aethiopicum strain GSKUMB [KJ21085] and F. culmorum strain GSKUMB [KJ190159] were grown in CYA broth and incubated at 27±2°C on the rotary shaker at 120 rpm for 21 days. At the end of incubation period, cultures were harvested for determination of fungal growth (biomass). The resultant culture filtrates were extracted twice with ethyl acetate and concentrated. One ml of final concentrate in methanol was employed for detection of DON and NIV with the help of RP-HPLC. Results: The highest amount of DON and NIV were produced by F. aethiopicum in the presence of D-mannose and D-galactose as C source, while the highest amount of biomass was recorded on maltose and succinic acid. F. culmorum produced maximum amount of toxins in the presence of D-glucose, D-mannitol and D-fructose. Sodium nitrate was most favorable nitrogen source as it induced maximum amount of toxins by F. aethiopicum, while L-methionine, L-asparatic acid and L-tryptophan were next preferred N source. In contrast, highest biomass of fungus was obtained with L-lysine, L-glutamine and L-tyrosine. F. culmorum produced maximum amount of toxin and biomass with potassium nitrate and L-tyrosine respectively. Conclusion: Present species of Fusarium differed varied both in toxins (DON, and NIV) and biomass production. Their response of fungi under investigation towards C and N sources is also varied.

Influence of different fusarium species on seed germination and seedlings growth of finger millet (Eleusine coracana L.) - Penugonda, Shilpa; Rao, Vankudoth Koteswara; Sivadevuni, Girisham; Reddy, Solipuram Madhusudhan (Indian Journal of Biotechnology, 2015)
Effect of agriculturally important Fusariumspecies on the seed germination and seedling growth of finger millet (Eleusine coracana L.) was investigated. Species of Fusarium caused significant seed germination inhibition and seedling growth which varied with the species and age of the culture. Culture filtrates of F. moniliforme, F. proliferatum, F. chlamydosporum, F. aethiopicum, F. heterosporum and F. sporotrichoides were comparatively more toxic. The correlation coefficients between polished and unpolished variety of fingermillet seed germination inhibition (0.574, P=0.005), shoot elongation inhibition (0.893, P=0.0000) and root elongation inhibition (0.175, P=0.1770) with culture filtrates of different species of Fusarium was recorded. Pathogenicity studies revealed that F. roseum, F.sporotrichoides, F. proliferatum and F.oxysporum caused seedrot and seedling death. The maximumroot elongation inhibition (52.20%), mean (36.39%) andminimum(14.73%)were recorded toward the toxicity of different species of Fusarium. Significant and positive correlation (0.802, P=0.0026) between the root and shoot, (0.393, P=0.130) between shoot and leaf, (0.121, P=0.369) between root and leaf elongation inhibition of finger millet could be observed. The culture filtrates ofmajormycotoxigenic strains of Fusariumrevealed production of Zearalenone (ZEA), T2 toxin, nivalenol (NIV), Deoxynivalenol (DON) and Deoxyscripenol (DAS). Toxicity of Fusarium species to its seed germination and seedling growth may be attributed to their secondary metabolites including mycotoxins.